The proteasome: A key modulator of nervous system function, brain aging, and neurodegenerative disease - Davidson, Kanisa; Pickering, Andrew M. (Frontiers in Cell and Developmental Biology, 2023)
The proteasome is a large multi-subunit protease responsible for the degradation and removal of oxidized, misfolded, and polyubiquitinated proteins. The proteasome plays critical roles in nervous system processes. This includes maintenance of cellular homeostasis in neurons. It also includes roles in long-term potentiation via modulation of CREB signaling. The proteasome also possesses roles in promoting dendritic spine growth driven by proteasome localization to the dendritic spines in an NMDA / CaMKIIα dependent manner. Proteasome inhibition experiments in varied organisms has been shown to impact memory, consolidation, recollection and extinction. The proteasome has been further shown to impact circadian rhythm through modulation of a range of ‘clock’ genes, and glial function. Proteasome function is impaired as a consequence both of aging and neurodegenerative diseases. Many studies have demonstrated an impairment in 26S proteasome function in the brain and other tissues as a consequence of age, driven by a disassembly of 26S proteasome in favor of 20S proteasome. Some studies also show proteasome augmentation to correct age-related deficits. In amyotrophic lateral sclerosis Alzheimer’s, Parkinson’s and Huntington’s disease proteasome function is impaired through distinct mechanisms with impacts on disease susceptibility and progression. Age and neurodegenerative-related deficits in the function of the constitutive proteasome are often also accompanied by an increase in an alternative form of proteasome called the immunoproteasome. This article discusses the critical role of the proteasome in the nervous system. We then describe how proteasome dysfunction contributes to brain aging and neurodegenerative disease.